Early blood-based microbiological testing is ineffective in severe stroke patients - Gumbinger, Christoph; Hug, Andreas; Mürle, Bettina; Berger, Benjamin; Zorn, Markus; Becker, Klaus-Peter; Zimmermann, Stefan; Dalpke, Alexander; Veltkamp, Roland (Journal of the neurological sciences, 2013)
Background and purpose: Patients with severe acute stroke are at high risk for systemic infections which are associated with an increase in morbidity and mortality; nevertheless current guidelines do not recommend prophylactic antibiotic therapy. Sensitive detection of pathogens in the blood is desirable to guide early antibiotic therapy. We studied the yield of blood culture testing and microbiological PCR-based methods for early detection of post-stroke bacteremia. Methods: Serial blood culture tests either during the first fever episode (>38.5°C) or 24h after admission were performed every 12h for up to 96h after admission. Additionally, microbiological PCR-based techniques for the detection of microbiological pathogens were performed once during the first fever episode prior to initiating antibiotic treatment. Results: 21 severely affected acute stroke patients deemed at high risk for systemic infections (median (interquartile range (IQR)) at admission NIHSSS 19 (15-30) were enrolled; 20 patients were intubated within 5h after ICU admission. All patients developed clinical signs and laboratory constellations compatible with systemic infections within 36h after admission. However, no patient had pathogenic bacteria either in serial blood culture analyses during the first 96h after admission or by PCR-based techniques. Conclusions: Very early bacteremia seems not to be a feature of severe stroke in patients despite signs of early immune system depression and frequent subsequent evidence of infection including pneumonia. Consequently our data suggests, that routine early blood-based standard or molecular microbiological assays do not reveal bacteremia, this finding questions the usefulness of their routine performance in this context.